Advancements of non-invasive prenatal testing: the role of obstetricians - Eltabbakh, Nada; Mohasin, Yalnaz; Jeddy, Rafiea (Frontiers in Medicine, 2024)
Since its debut in 2011, Non-Invasive Prenatal Testing (NIPT) has continually demonstrated its effectiveness in detecting an expanding number of diseases. NIPT offers a less invasive approach to prenatal chromosomal disease screening, providing prospective parents with vital information to better prepare for their potential pregnancy outcomes. NIPT was primarily designed for screening trisomy 13, 18, and 21. However, its scope has since broadened to encompass microdeletions and autosomal dominant monogenic diseases. Conversely, the normalization of NIPT can have unintended consequences. Some patients opt for NIPT without any medical indications, driven by a desire to remain cautious. This over-screening for chromosomal abnormalities can exacerbate pregnancy-related anxiety, as individuals might feel pressured into taking the test unnecessarily. While NIPT can be highly successful when conducted correctly, it is not infallible, and obstetricians play a crucial role in managing patient expectations. This includes providing genetic counseling to individuals with relevant genetic information regarding their personal and family histories. In the context of NIPT, a bioinformatics analysis is performed on a cell-free DNA (cfDNA) sample extracted from the mother's placenta to determine the fetal fraction (FF). This FF measurement is vital for quality control and ensuring statistical confidence in the test results. Raising awareness among clinicians about the significance of FF enhances patient care and alleviate concerns about the possibility of failed NIPT. This paper aims to explore the ongoing debates and more specifically the significance and pitfalls of NIPT on a psychosocial and ethical scale, all while highlighting the importance of genetic counseling.